Third and mixed conditionals. - Quijije Menoscal, Noemi Yajaira (2022)
The second component of the complex exam is the demonstrative class that was developed at the prestigious State University Peninsula of Santa Elena in the School Sciences and Languages, located in the province of Santa Elena, which aimed to assess the teaching abilities of the students. Therefore, the demonstration class is the second component of the complex exam. The objective of this report is to present each of the details and evidence that was carried out in the process of the demonstration class. The demonstration class is considered an effective method to measure the abilities of students as future teachers. In the process of this evaluation, the student must demonstrate command of the stage, command of the English language and use of teaching methods.